Stylistic reproduction in the English version of Winter Pasture from the perspective of the stylistic markers theory - Liu, Yunyue (Nanyang Technological University, 2023)
Winter Pasture is a translated non-fiction book by Li Juan about the disappearing Kazakh nomadic life in Xinjiang. It manifests a unique narration style that poetically narrates Kazakh herders' lives, culture, and customs while delivering Li Juan's personal feelings and thoughts throughout the book. The literature rating platforms from both the Chinese and the English-speaking worlds confirm the success of Winter Pasture, making it an important part of our ethnography and our understanding of human history. However, studies on the translations of Winter Pasture and Li Juan's other works are scarce, leaving quite a large gap in the scholarship and obscuring her abilities to bring her style successfully to the English-speaking world. Based on the Stylistic Markers Theory by Liu Miqing, the author of this paper classifies the style of Winter Pasture according to the features of formal markers and conducts a comparative study with qualitative analyses. And this paper finds that the translators use various modes to transfer different formal markers, including onomatopoeic words at the phonological level, the Romanised Kazakh vocabularies and the language of Kazakh grammar at the register level, meaningful punctuation at the syntactic level, the skilful uses of loose sentences and harmonious parallel sentences at the textural level, and the detailed colour words at the lexical level. Thus, the translation methods employed to transfer the style and to maintain popularity in the target market are found, contributing to the translation of other Li Juan's works and non-fiction books about the Kazakh nomadic culture.